Teori Belajar Humanistik Dan Implikasinya Pada Maharah Istima' - Naning Ma’rifatul Faiqoh; R. Umi Baroroh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
Recently, many educational theories grow up based on the assumptions in some problems. This article explores humanistic learning theory and its implications for learning Arabic at maharah istima ', using library research, since the data and information were collected in the form of a continuous library with discussion, then the researcher analyzed the data using content analysis method. The results shows that the application of maharah istima ' learning Arabic includes learning objectives, learning models, using media, culture and students’ background. Carl Rogers' humanistic theory emphasizes deep humanity, does not contain selfish, individualistic elements or authoritarian, they do not have to follow our opinion, so this theory focuses on the student center, that focused on the cognitive, affective and psychomotor aspects by giving students their rights, being humanized, recognized and accepted, from which students will be optimistic in voicing contents of their mind.